Genome-Wide Annotation and Expression Profiling of Cell Cycle Regulatory Genes in Chlamydomonas reinhardtii - Bisova, Katerina (American Society of Plant Biologists, 2005)
Eukaryotic cell cycles are driven by a set of regulators that have undergone lineage-specific gene loss, duplication, or divergence in different taxa. It is not known to what extent these genomic processes contribute to differences in cell cycle regulatory programs and cell division mechanisms among different taxonomic groups. We have undertaken a genome-wide characterization of the cell cycle genes encoded by Chlamydomonas reinhardtii, a unicellular eukaryote that is part of the green algal/land plant clade. Although Chlamydomonas cells divide by a noncanonical mechanism termed multiple fission, the cell cycle regulatory proteins from Chlamydomonas are remarkably similar to those found in higher plants and metazoans, including the proteins of the RB-E2F pathway that are absent in the fungal kingdom. Unlike in higher plants and vertebrates where cell cycle regulatory genes have undergone extensive duplication, most of the cell cycle regulators in Chlamydomonas have not. The relatively small number of cell cycle genes and growing molecular genetic toolkit position Chlamydomonas to become an important model for higher plant and metazoan cell cycles.